A systematic literature review of online religious leaders, digital advertising, management performance, and consumer decisions in Islamic Banking - Mulyanti, Kurniawati; Nugroho, Aris Setyanto; Darmansyah, Darmansyah (Journal of Economics and Business Letters, 2025)
This study systematically reviews the literature to examine how online religious leaders, digital advertising, and management performance influence consumer decisions to adopt Islamic banking products, with a focus on Bank Syariah Indonesia (BSI). Employing a systematic literature review methodology, 118 studies published between 2005 and 2025 were analyzed using thematic synthesis. The findings reveal that these three antecedents impact consumer behavior through the mediating roles of trust and motivation. Online religious leaders build legitimacy and shape subjective norms, while digital advertising engages consumers through credibility and emotional appeal. Management performance reinforces service quality, innovation, and Sharia governance, enhancing trust. The integration of the Theory of Reasoned Action (TRA) and the Stimulus-Organism-Response (SOR) model provides a robust theoretical lens to understand these dynamics. The study contributes to academic discourse by contextualizing behavioral theories in Islamic banking and offers practical guidance for banks to develop culturally sensitive, ethically compliant, and effective marketing and management strategies.